2016
DOI: 10.1155/2016/3264172
|View full text |Cite
|
Sign up to set email alerts
|

A Case Report of Isolated Cuboid Nutcracker Fracture

Abstract: Isolated cuboid fractures are very rare, since they typically occur in combination with midfoot fractures or dislocations. A 61-year-old man presented at our hospital with pain and swelling on the outside of his right foot. The lateral column of his right foot was shortened by approximately 6.5 mm on X-ray. CT showed displacement of the joint surface between the cuboid and the fourth metatarsal, with a 3.5 mm depression. An MRI revealed no other injuries. Based on these findings, we diagnosed the patient with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 5 publications
0
5
0
Order By: Relevance
“…The majority of the evidence reporting on the functional outcomes following cuboid fracture fixation comes from case reports [ Table 1 ]. 1 9 19 20 23 24 25 26 27 28 29 The outcomes presented by these studies are favorable. In two small case series involving four patients each, the authors reported no complications and good function postoperatively.…”
Section: Surgical Fixation: Outcomesmentioning
confidence: 81%
“…The majority of the evidence reporting on the functional outcomes following cuboid fracture fixation comes from case reports [ Table 1 ]. 1 9 19 20 23 24 25 26 27 28 29 The outcomes presented by these studies are favorable. In two small case series involving four patients each, the authors reported no complications and good function postoperatively.…”
Section: Surgical Fixation: Outcomesmentioning
confidence: 81%
“…“Due to the limited number of reported cases of nutcracker fractures, the best method of treatment has not been determined” [ 12 ]. Ohmori et al reported a “new treatment plan” for an isolated nutcracker injury—arthroscopic elevation of depressed bone fragments and the use of a bone biopsy needle to fill in the large defect with artificial bone [ 13 ]. Nondisplaced fractures may be treated with a short leg cast and non-weight-bearing status [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Cuboid fractures are uncommon in sports, with isolated cuboid fractures being rare 1,8 because they typically occur in combination with other fractures or dislocations about the foot and ankle. Anatomy and function as it relates to the foot biomechanics is important because, once disrupted, they are the main factors that underlie the concern for potential complications.…”
Section: Implications For Clinical Practicementioning
confidence: 99%
“…Isolated cuboid fractures are rare because cuboid fractures typically occur in combination with other midfoot fractures or dislocations. 1 A 5-year study demonstrated an annual incidence of midfoot fractures as 3.6 in 100,000 per year in the United Kingdom, of which the cuboid accounted for 50% of all midfoot fractures. 2 The cuboid bone has six surfaces, four of which articulate with surrounding bony structures (Figure 1).…”
mentioning
confidence: 99%